Modeling the growth and migration of sandy shoals on ebb‐tidal deltas. Issue 7 (25th July 2016) - Ridderinkhof, W.; de Swart, H. E.; van der Vegt, M.; Hoekstra, P.
Abstract: Coherent sandy shoals that migrate toward the downdrift coast are observed on many ebb‐tidal deltas. In this study, processes that cause the growth and migration of shoals on ebb‐tidal deltas are identified. Moreover, the effect of the incident wave energy and the tidal prism of an inlet on the migration speed of these shoals is investigated. For this, a numerical morphodynamic model with an idealized geometric setup is employed. The model computes the bed level evolution due to local erosion and deposition of sand driven by tides and waves. Analysis of model results shows that shoals grow when there is a local imbalance between the bathymetry and the wave conditions, which in this study was imposed by manually breaching the ebb‐tidal delta or by adding storms to the wave forcing. There are thresholds for shoal formation that depend on the distribution of the sand and the incident wave energy. Wave refraction over the shoals leads to focusing of wave energy and increased wave energy dissipation around the location of the local minimum water depth. This generates residual currents over the shoal and increased skin friction toward the local minimum water depth, which together create a sand transport pattern that induces the growth and migration of the shoal. Sand transport due to asymmetric waves contributes to keeping the shoal a coherent structure. The shoal migration speed increases with increasing incident wave energy and decreasing tidal prism; this is because tidal residual currents oppose the wave‐driven residual currents that cause shoal migration. Key Points: Storms trigger the formation of shoals on ebb‐tidal deltas A local imbalance between the bathymetry and wave conditions causes shoals to grow Shoal migration speed increases with increasing incident wave energy and decreasing tidal prism